Aplikasi Model Static dan Dynamic Location Quotients dan Shift-Share dalam Perencanaan Ekonomi Regional, Studi Kasus Kabupaten Ogan Komering Ulu Propinsi Sumatera Selatan - Nazipawati Nazipawati (Jurusan Ilmu Ekonomi dan Studi Pembangunan Universitas Jenderal Soedirman, 2007)
The purposes of this research are: to identify the basic economic sectors of Ogan Komering Ulu (OKU) regency, and to know economic growth components of regency compared with the economic of South Sumatera Province. Used analysis tools are Static Location Quotient (SLQ), Dynamic Location Quotient (DLQ) and Shift-Share. The compare of SLQ and DLQ results show that OKU regency has basic economic sectors for now and the future in trade, restaurant and hotel sector, finance, construction rent enterprise service sector and services sector. In addition OKU regency have basic economic sectors for the future in mining and quarrying sector, manufacture sector, electricity, gas and water supply sector, construction sector and transportation and communication sector. Whereas shift-share analyzes results shows that economic sector growth has increased in 2003-2005 period in OKU regency, and the industrial mix shows negative result. Furthermore, OKU regency has no competitive advantages.Keywords: Static and Dynamic Location Quotients, Shift Share, Ogan Komering Ulu